Prevalence of infection in feral cats in Massachusetts - Erin R Galemore; Mary A Labato; Elizabeth O’Neil (Journal of Feline Medicine and Surgery Open Reports, 2018)
Objectives The primary objective of this study was to determine the prevalence of Anaplasma phagocytophilum infection and exposure in adult feral cats in Massachusetts, an endemic area for A phagocytophilum and its tick vector Ixodes scapularis . The secondary objective was to determine if there were correlations between A phagocytophilum infection and the presence of anemia and thrombocytopenia. Methods Blood samples were collected between June and December 2015 from 175 apparently healthy adult feral cats that were presented to trap and release spay/neuter centers in Massachusetts. Complete blood count, blood smear evaluation, SNAP 4Dx Plus test (IDEXX) and A phagocytophilum PCR were performed on all samples to document acute infection (PCR-positive and/or inclusions observed on blood smear) and exposure to A phagocytophilum (SNAP 4Dx Plus-positive for A phagocytophilum antibodies). Results The prevalence of exposure to A phagocytophilum in feral cats in Massachusetts was 9.7%, whereas the prevalence of acute infection was 6.9%. All blood smears were negative for Anaplasma species inclusions; therefore, acute infection was defined as testing positive on PCR analysis. No statistically significant correlations were identified for cats that were positive for A phagocytophilum on PCR analysis or SNAP 4Dx Plus test and the presence of anemia or thrombocytopenia. Conclusions and relevance The prevalence of A phagocytophilum exposure in feral cats approaches 10% and is higher than the previously reported national average prevalence of 4.3% in the USA. A phagocytophilum infection may be an emerging infectious disease in cats. Further research is needed to determine the prevalence of clinical illness associated with A phagocytophilum infection in cats living in endemic areas.